Loss of paraspinal muscle mass is a gender‐specific consequence of cirrhosis that predicts complications and death. Issue 11 (11th November 2018) - Engelmann, Cornelius; Schob, Stefan; Nonnenmacher, Ines; Werlich, Luise; Aehling, Niklas; Ullrich, Sebastian; Kaiser, Thorsten; Krohn, Sandra; Herber, Adam; Sucher, Robert; Bartels, Michael; Surov, Alexey; et al.
Summary: Background: Loss of skeletal muscle mass is a recognised complication with a prognostic impact in patients with cirrhosis. Aim: To explore in a retrospective analysis which muscle compartment most reliably predicts the occurrence of cirrhosis‐associated complications and if there are gender‐related differences. Methods: 795 patients with cirrhosis listed for liver transplantation between 2001 and 2014 met the inclusion and exclusion criteria including an abdominal CT scan (±200). Controls were 109 patients who underwent a CT scan after polytrauma. The paraspinal muscles index (PSMI), the abdominal wall muscles index (AWMI) and its combination skeletal muscle index (SMI) were assessed at L3/L4, normalised to the height (cm 2 /m 2 ). Results: 62.0% of patients with cirrhosis had alcoholic liver disease, and 70.6% were male. As compared to controls, a reduction in PSMI and SMI but not AWMI was associated with high model of end‐stage liver disease (MELD) score, high Child‐Pugh class, and the presence or history of cirrhosis‐associated complications in males but not females. PSMI independently predicted the occurrence of bacterial infections (HR 0.932), spontaneous bacterial peritonitis (HR 0.901), hepatic encephalopathy (HR 0.961), and hepatorenal syndrome (HR 0.946) by multivariate Cox regression analysis in a gender‐independent manner. Post‐transplant survival was not associated with the PSMI; neither AWMI nor SMI predicted any clinical endpoints. Conclusions: This study links muscle wasting in patients with cirrhosis predominantly to males. However, the presence of a low PSMI mass is a gender‐independent predictor of developing cirrhosis‐associated complications and death. Scores combining the MELD with muscle parameters should be re‐validated by utilizing the PSMI. Abstract : LINKED CONTENT This article is linked to Sinha and Engelmann et al papers. To view these articles visit https://doi.org/10.1111/apt.15070 and https://doi.org/10.1111/apt.15086 .